Design and Development of Nocturnal Water Cooling System for Building Space Cooling in Malaysian Tropical Climate - Muhammad Syukri, Imran (Universiti Malaysia Sarawak (UNIMAS), 2017)
Building particularly in hot climate like Malaysia would require mechanical means of cooling such as the air conditioning system to cool down the building to an extent that the building becomes more dependent on air conditioning system as well as use of electrical energy. This use of cooling energy translates to higher world fuel demand as well as more CO2 release to the environment. Eventually resource conservation and global climate change drive forces building owner to go green as well minimize energy use that extends into the area of building cooling method. More sustainable building cooling methods is being explored and tested to conserve energy while maintaining an acceptable indoor thermal condition. A prototype hydronic radiator panel activated with natural heat sink source such as nocturnal or night cooling have been developed and tested in a test room under Malaysian climate condition. The experiment was also complemented by simulation using Energy Plus to predict the thermal condition as well as impact to energy consumption for several selected buildings.